Knowledge of Libyan dentists about vertical root fractures (VRF): A survey study (Benghazi dentists as a case study). - Alawjali, Samia S.; El kumati, Iman A.; Alfeitouri, Fatma O. (Libyan Journal of Science &Technology, 2025)
The aim of the present study was to assess the knowledge of Libyan dentists about vertical root fractures (VRF), causes, clinical signs and symptoms, diagnosis and treatment and to find out the relationship between the knowledge and sociodemographic data of the dentists. Materials and Methods: This was a descriptive cross-sectional study. The survey was carried out in Benghazi (Libya) in 2021. 375 dentists were invited. Data were collected using an electronic questionnaire. The questionnaire is designed to consist of two parts; the first part deals with the demographic characteristics of the participants and the second part is divided into four aspects to assess the knowledge of participants about VRF; (the definition and general information of VRF, the signs, symptoms, and diagnostic process of VRF, factors that contribute to VRFs and the preferred treatment of VRF in single-root and multi-rooted teeth). The survey data were statistically analyzed using Fisher’s Exact test. Results: The survey response rate was 375/225(60%). Almost half of respondents 112 (49.8%) had moderate Knowledge score about (definition and general information of VRF) and (the signs, symptoms and diagnostic process of VRF). The relationship between the knowledge score of the Libyan dentists regarding the signs, symptoms and diagnostic process of VRF and (gender, Specialization) was statistically significant difference p value < 0.05. The male participants in this study had higher knowledge score than female regarding this section. The endodontists had a higher knowledge for diagnosis of VRF than others did. More than half (63.1%) and Almost half (46.2%) of respondents had high knowledge scores about contributing factors to the susceptibility of root to fracture and the preferred treatment for VRF in single and multi-rooted teeth, respectively. The relationship between the knowledge score of the Libyan Dentists regarding the preferred treatment for VRF in single and multi-rooted teeth and gender was a statistically significant difference p value <0.05. The male participants in this study had higher knowledge score than female participants regarding the preferred treatment for VRF. Conclusion: This study showed that around half of the participants had moderate to high knowledge regarding to different aspects of VRF.